What the ladybug heard - Donaldson, Julia; Monks, Lydia (London : Macmillan, 2009)
Although much quieter than the farm animals that moo, cluck, or oink, a gentle ladybug is instrumental in foiling a plan to steal the farm's prize-winning cow.
Booklist, February 2010.
Kirkus Review, April 2010.
School Library Journal, April 2010.
1.8
K-3
Keywords: Animal sounds -- Juvenile fiction; Domestic animals -- Juvenile fiction; Ladybugs -- Juvenile fiction; Thieves -- Juvenile fiction; Animal sounds -- Fiction; Domestic animals -- Fiction; Ladybugs -- Fiction; Robbers and outlaws -- Fiction; Stories in rhyme; Animal sounds -- Fiction; Domestic animals -- Fiction; Ladybugs -- Fiction; Stories in rhyme; Thieves -- Fiction; Picture books for children